2016
DOI: 10.1038/srep23834
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Angiotropism/Vascular Co-Option in a Murine Model of Brain Melanoma: Implications for Melanoma Progression along Extravascular Pathways

Abstract: Angiotropism/pericytic mimicry and vascular co-option involve tumor cell interactions with the abluminal vascular surface. These two phenomena may be closely related. However, investigations of the two processes have developed in an independent fashion and different explanations offered as to their biological nature. Angiotropism describes the propensity of tumor cells to spread distantly via continuous migration along abluminal vascular surfaces, or extravascular migratory metastasis (EVMM). Vascular co-optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 43 publications
(67 reference statements)
6
70
0
3
Order By: Relevance
“…An increasing amount of evidence generated using intravital microscopy reveals that migration tracks are not created solely by matrix remodelling but also occur naturally in healthy tissues 6,11 . Examples include tracks along ECM fibres in the interstitial space 7,9,11 , between muscle and nerve fibres 11 , along or within blood vessels 23,24 and in the vasculature of target organs 25,26 . The different forms of migration tracks are illustrated schematically in FIG.…”
Section: Cell Confinement In Vivomentioning
confidence: 99%
“…An increasing amount of evidence generated using intravital microscopy reveals that migration tracks are not created solely by matrix remodelling but also occur naturally in healthy tissues 6,11 . Examples include tracks along ECM fibres in the interstitial space 7,9,11 , between muscle and nerve fibres 11 , along or within blood vessels 23,24 and in the vasculature of target organs 25,26 . The different forms of migration tracks are illustrated schematically in FIG.…”
Section: Cell Confinement In Vivomentioning
confidence: 99%
“…neuroserpin, serpin B2) block the anti-metastatic effects of plasmin to promote vascular co-option, creating a microenvironment that is conducive to migration and colonization (Valiente et al, 2014). Similarly, another recent study used high-resolution imaging techniques to show that melanoma metastases within the brain exhibit angiotropism and vascular co-option to facilitate cancer cell spreading within the brain parenchyma (Bentolila et al, 2016). Whether these processes also occur in primary brain tumors is less well understood; however, vascular co-option as a potential compensatory mechanism for angiogenesis has major implications for patients with highly vascularized tumors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Lugassy et al 66 identified that genes involved in inflammation (CCL2, IL6, TRAF1, CXCL6, SELE, ICAM1, SLC7A2, C2CD4B, PDGFB, and SERPINB2) were expressed in melanomas as a result of the interaction of melanoma cells and endothelial cells. More recently, Bentolila et al 67 described the perivascular migration of serpin B2-expressing melanoma cells, without associated intravasation; serpin B2 expression was also noted in angiotropic human melanoma brain metastases. Thus, it has been proposed that neutrophilic inflammation present in ulcerated melanomas may contribute to pericyte mimicry, angiotropism, and subsequent metastasis.…”
Section: Extravascular Migratory Metastasis and Angiotropismmentioning
confidence: 99%